Do determinants of hypertension status vary between Ghana and South Africa? Study on global AGEing and adult health - Capistrant, Benjamin; Charlton, Karen; Snodgrass, Josh; Kowal, Paul (SA Heart Journal, 2019)
Objectives: Determinants of hypertension prevalence, diagnosis and control are poorly understood in sub-Saharan Africa, including whether these determinants vary between and among countries. Methods: A cross-sectional analysis of Study on global AGEing and adult health (SAGE) data, nationally representative samples of adults aged 50+ (n=3 458 South Africa; n=4 196 in Ghana). Hypertension prevalence and status (awareness, treatment and control) were determined from directly measured blood pressure and respondents’ self-reported history of hypertension diagnosis and current treatment status. Sex-stratified, multivariable adjusted logistic regression models were used to test cross-country differences in demographic, socio-economic, environmental, and health-related determinants of hypertension prevalence and status. Results: South Africans had higher age-standardised prevalence of hypertension (Men: 76%, Women: 82%) compared to Ghana (Men: 57%, Women: 61%). Odds of hypertension prevalence varied for rural residence and education varied between country. Consistent differences in awareness of hypertension between countries included education, income, and weight status by sex; sex-specific differences between countries were also apparent. Determinants of control and management of hypertension (education) differed between countries only for women. Conclusions: Behavioural, environmental, and social determinants all influence hypertension prevalence and status for middle and older-age adults in sub-Saharan Africa, although differently between countries.